Cultivar-Specific Hormesis Effects of Silver Nanoparticles on Maize Growth are Linked to Rhizosphere Microbial Mommunities of two Maize Cultivars - Siyao Li; Naijia Guo; Haiying Zhao; Zhiyuan Liu; Chengheng Fan; Fengying Li; Jiling Cao (Journal of Soil Science and Plant Nutrition, 2026)

Laser-implanted interstitial hydrogen as dynamic electron modulator activates quaternary nanoalloys for ultrahigh HER activity & stability - Guoshuai Fu; Xiaoliang Yuan; Yuexin Xie; Jiling Li; Pu Liu; Guowei Yang (Chemical Engineering Journal, 2026)

Bisphenol P triggers hepatic injury via gut microbiota dysbiosis–Induced intestinal barrier disruption - Nana Ma; Hang Ren; Zihan Ma; Ryoiti Kiyama; Jiling Liu; Lei Wang; Aiwen Wang; Mengyi Wei; Yulang Chi; Linying Jia; Xinyi Peng; Jiaqi Wu; et al. (Journal of Environmental Management, 2026)

Effect of nutrient addition and mowing on plant diversity and soil carbon content of meadow steppe in Inner Mongolia - Huayi Zhang; Chenxu Liu; Jiling Tan; Weiheng Bi; Xuefeng Chen; Bo Bai; Namuhan; Wuyunna; Guangdi Li; Yantao Song (Journal of Environmental Management, 2025)

Formation of metal-microplastic complexes in lung adenocarcinoma is associated with increased risk of cancer progression - Runze Liu; Xiaokang Guo; Guangjian Yang; Shuangqing Lu; Feihu Chen; Wenxiao Jia; Ji Li; Jiling Niu; Hongbo Guo; Hui Zhu (Journal of Hazardous Materials, 2025)

Review of glass-ceramics: Solidification of toxic elements and durability - Qiong Li; Bo Liu; Jiling Liu; Qian Zhang; Changcong An; Zhe Sun; Bakhtiyor Pulatov; Siyu Wei; Jiaxing Fan (Waste Management, 2025)

Warming mitigates the effects of nitrogen addition on the soil diazotrophic community in a subtropical forest - Jiling Cao; Lin Li; Yu Han; Zhiyuan Liu; Faying Lai; Yusheng Yang (Applied Soil Ecology, 2024)

Structure modification and anti-tumor activity evaluation on sesquiterpene lactones TBA and TBB from Sphagneticola trilobata - Zhou Xiuqiao; Yi Jiling; Chen Guangying; Liu Zhixiang; Hui Yang; Chen Wenhao (Natural Product Research, 2023)

Highly synergistic and polarized KNbO3/WO3 heterojunction for piezo-photocatalytic degradation of organic pollutant - Rui Huang; Wei Cai; Heng Zhang; Zhenhua Wang; Qin Zhang; Rongli Gao; Gang Chen; Xiaoling Deng; Xiang Lei; Jiling Dong; Xiaoyan Liu; Chunlin Fu (Journal of Environmental Chemical Engineering, 2023)

Effects of copper oxide nanoparticles on soil diazotrophic communities in maize rhizosphere - Jiling Cao; Zhiyuan Liu; Haiying Zhao; Faying Lai; Yu Han; Xiangui Lin (Journal of Soils and Sediments, 2023)

Protein kinase Ime2 is associated with mycelial growth, conidiation, osmoregulation, and pathogenicity in Fusarium oxysporum - Jiling Xiao; Yi Zhang; Ke Yang; Yanying Tang; Lin Wei; Erming Liu; Zhihuai Liang (Archives of Microbiology, 2022)
Fusarium oxysporum f.sp. niveum is one of the most serious diseases impairing watermelon yield and quality. Inducer of meiosis 2 (Ime2) is the founding member of a family of serine/threonine protein kinases and plays important roles in yeasts and other filamentous fungi. In this study, we analyzed the functions of Fo Ime2, the ortholog of Saccharomyces cerevisiae Ime2 in F. oxysporum f.sp. niveum . The FoIme2 -deleted mutants exhibited obvious morphological abnormalities, including slower vegetative growth, more branches in the edge hyphae and a reduction in conidia production. Compared to the wild type, the mutants were hypersensitive to the osmotic stressor NaCl but were more insensitive to the membrane stressor SDS. The deletion of FoIme2 also caused a reduction in pathogenicity. Transcriptional analysis revealed that Fo Ime2 acts downstream of Fo Opy2 which is an upstream sensor of the MAPK kinase cascade. These results indicate that Fo Ime2 is important in the development and pathogenicity of F. oxysporum, and provide new insight for the analysis of the pathogenic mechanism of F. oxysporum.

A Multi-Level Analysis of the Effects of Epoch Length on the Estimates of Children’s Moderate to Vigorous Physical Activity - Han Chen; Jiling Liu (Journal of Science in Sport and Exercise, 2022)

A new species of Devriesia causing sooty blotch and flyspeck on Rubber Trees in China - Wenhuan Li; Yunxue Xiao; Chunsheng Wang; Jiling Dang; Chen Chen; Liu Gao; Jean C. Batzer; Guangyu Sun; Mark L. Gleason (Mycological Progress, 2013)